(untitled) (PANGEEA, 2025)
Environmental education through the educational and extracurricular activities. The paper presents some aspects of environmental education in schools, emphasizing its importance in training students a realistic outlook on the world and life. In this context it stresses the need for disciplines that ensure the implementation of this goal to enjoy a realistic status.